Associação de esquemas iniciais desadaptativos em transtornos do eixo I - Seixas, Carlos Eduardo (2014)
The present study aimed to assess whether there is an association of Early Maladaptive Schemas (EMS) in acute Axis I disorders in a mixed clinical population of 21 women and 10 men, aged between 18 and 57 years. For this purpose, two evaluation instruments were used: the Young Schema Questionnaire - Short version (YSQ-S3) and the MINI diagnostic interview Plus Version 5.0.0. For this method, cross-sectional descriptive study with a quantitative approach was performed. The sample allowed us to evaluate the association of EMS with the diagnostic category of anxiety, mood, bipolar disorder, generalized anxiety disorder (GAD) and comorbid panic disorder with agoraphobia and GAD. After collecting data, the data were subjected to statistical analyzes, performed by Fisher's exact test procedures. The results were the significance p 043 Subjugation of the EID for the group of anxiety disorders and a significance p 048 second schematic Domain - Autonomy and impaired performance for comorbid panic disorder with agoraphobia and GAD, compared to other diagnostic found in studies of anxiety. No associations of EMS for bipolarity GAD and mood disorders were found. The current literature indicates that the Schema Theory has been applied most often to personality disorders, however the stability of Early Maladaptive Schemas combine as a vulnerability factor for mood disorders and anxiety. Therefore, Schema Therapy has shown relevance for acute disorders, especially among the more chronic cases of mood and anxiety disorders, which have high levels of EMS. Research is needed to strengthen this assertion and better identify cases that may benefit most.